Effect of Hearing Impairment on Behavior and Communication of Children in Schools and Special Education Centers in Mosul City (Medico Legal Update, 2020)
Objectives: To identify the effect of hearing impairment on children behavior in daily activities andcommunication with peers and problems facing teachers of HI children in Iraqi environment. Methods : the strength and difficult questionnaire (SDQ) was used to measure the behavioral, and peer problemsquestionnaire to measure communication disorders of children with HI based on parents and teachers in(209) children (123) HI and (86) normal hearing control group. Results: on parent teacher questionnairesignificantly higher behavioral problems for HI children compared with control group (p-value 0.043< alpha value 0.05) and (chi-square 7.321) so increase the emotional problems (p-value 0.035)and peerproblems (0.026) of HI children its highly significant found of behavioral problems, so 65% of hearingimpaired children had communication problems with others and environment. The teachers facing manyproblems when deals with HI but the most common one difficult when communicate with them because thelimited capabilities available and modern educational methods for teaching the HI children. Conclusions: The majority of hearing impaired children have congenital cause for their hearing loss. Behavior problemsappear more common in children with hearing loss and communication problems. The vast majority ofteachers agree that there are problems facing students with hearing impairment, and these difficulties needto be dealt with the benefit of their children and the community as a whole.